2001
DOI: 10.1302/0301-620x.83b4.0830598
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of two different types of alumina-alumina hip prosthesis retrieved for aseptic loosening

Abstract: W e compared and quantified the modes of failure and patterns of wear of 11 Mittelmeier and 11 Ceraver-Ostal retrieved alumina-alumina hip prostheses with reference to the corresponding clinical and radiological histories.Macroscopic wear was assessed using a three-dimensional co-ordinate measuring machine. Talysurf contacting profilometry was used to measure surface roughness on a microscopic scale and SEM to determine mechanisms of wear at the submicron level.The components were classified into one of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
71
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 8 publications
11
71
1
Order By: Relevance
“…SEM revealed that the polished surface of the alumina was extensively scratched in this scar. This finding is similar to those reported by Nevelos et al 12,14,15 . Such stripe scars have not been observed in conventional hip simulator experiments.…”
Section: Discussionsupporting
confidence: 93%
“…SEM revealed that the polished surface of the alumina was extensively scratched in this scar. This finding is similar to those reported by Nevelos et al 12,14,15 . Such stripe scars have not been observed in conventional hip simulator experiments.…”
Section: Discussionsupporting
confidence: 93%
“…Boutin and Blanquaert [8] reported a mean rate of wear of 9 lm per year for the femoral head and 6 lm per year for the acetabular socket with use of the same ceramic-onceramic bearing surface as reported in this series. Nevelos et al [26] reported the same results for hips implanted by Sedel et al [31] with the same followup. In our series, with the radiographic technique of evaluation, the decentering of the femoral head in AL-AL hips ranged between 0 and 20 lm per year (average 13 lm per year).…”
Section: Discussionsupporting
confidence: 56%
“…However, in our current study, the CoCr cup rims showed neither rim distortion nor notching. Therefore, femoral notching in our cases was a result of the cup rim habitually tracking across the same site on the neck, thereby producing wear over many repetitive impingement episodes [63,64,67].…”
Section: Discussionmentioning
confidence: 92%